Mer côtière à forte pression anthropique propice au développement d’une gestion intégrée : exemple du bassin oriental de la Manche (Atlantique Nord-Est) - Jean-Claude Dauvin; Olivier Lozachmeur (VertigO)
The eastern English Channel: a coastal sea in the northeastern Atlantic, subjected to heavy anthropogenic pressure, propitious for an integrated management plan. An epi-continental sea with a megatidal regime, the English Channel constitutes an important northwestern European crossroads, both in economic and bio-geographical terms. Its shallow eastern basin (< 50 m) is home to many new maritime activities, including energy production (e.g., thermo-nuclear power plant, offshore wind mill), marine resource exploitation (e.g., aggregate extraction), and increased portuary activity (e.g., greater capacity for container unloading). This anthropogenic pressure has led to the progressive deterioration of the environmental quality of the milieu, particularly at the mouth of the Seine estuary. To try to better understand the stakes and respond to these pressing problems, both national and European measures designed to increase knowledge about this international coastal zone have been instituted over the last dozen or so years, with an eye towards developing an integrated management plan for the zone. To this end, several interdisciplinary scientific programs have been implemented, both at the national and international level, to study all or parts of the eastern English Channel. Only by such a combined effort can the knowledge of the diverse eco-socio-systems in this territory be taken into account and their many interactions analyzed. During this same period, numerous qualified stakeholders have attempted to initiate integrated coastal zone management (ICZM) policies. The French national government intervenes through its Ministries, prefectures and decentralized services. The territorial authorities—including both regional and local authorities, as well as syndicats mixtes (groups combining several different levels from local to regional)—also play an increasingly important role in coastal zone management. The configuration of the French public administration has evolved in recent years, allowing a variety of initiatives, spanning a national to local gamut, to be undertaken in an attempt to better coordinate the actions in the eastern English Channel.